Enhancing voltage stability in active distribution networks through solar PV integration - Dhandapani, Lakshmi; Sreenivasan, Pushpa; Murugan, Sangeetha; Maria, Helaria; Banerjee, Sudipta (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
Solar PV's explosive expansion is changing distribution networks and posing new problems, such as bidirectional power flow, unstable voltage, and power quality problems, particularly in networks with low X/R ratios. Abrupt changes in voltage are difficult for conventional voltage control techniques like shunt capacitors and on-load tap changers (OLTCs) to handle. IEEE Standard 1,547 has little efficacy in such networks, despite the fact that PV inverters may provide reactive power. This paper suggests a real-time coordinated control approach to improve voltage regulation by combining PV inverters, OLTC, and battery energy storage systems (BESS). Reactive power from PV inverters is prioritized to lower operational expenses and reliance on BESS. Better voltage stability, a decrease in BESS energy processing from 9400.3 kWh to 1701.87 kWh, and a reduction in OLTC activities are the outcomes. Rural networks gain from the strategy's ability to support smaller, more affordable BESS units’ voltage sensitivity analysis, and ideal BESS sizing may be investigated in future studies.